Chyloma formation after anterior cervical disc fusion. Issue 12 (26th August 2020) - Klug, Theodore; Sebelik, Merry; Shires, Courtney B.
Abstract: Chyle leak from iatrogenic thoracic duct injury is a rare but serious complication of head and neck surgery. The chyloma in this case took months to recognize and required open thoracic ligation. He fully recovered. Abstract : Chyle leak from iatrogenic thoracic duct injury is a rare but serious complication of head and neck surgery. The chyloma in this case took months to recognize and required open thoracic ligation. He fully recovered.